Systematic Desensitization Techniques in Overcoming Specific Phobias in Adolescents - Rizki Dwi Bakhtiar Surin; Nindia Pratitis; Aliffia Ananta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study explores systematic desensitization therapy in addressing specific phobias among adolescents, particularly arachnophobia, ophidiophobia, and katsaridaphobia. The research aims to explore the subjective experiences of adolescents undergoing systematic desensitization for specific phobias, focusing on perception and emotional changes. A qualitative phenomenological method was employed to delve into the subjective experiences of adolescents with specific phobias. Data were collected through interviews, observations, and document analysis, and analyzed using Interpretative Phenomenological Analysis (IPA), with validity ensured through triangulation and member checking. Findings indicate that adolescents experienced significant anxiety reduction and decreased avoidance behaviors, thanks to therapist support and the application of relaxation techniques. This study highlights the importance of understanding individual experiences to enhance the effectiveness of therapeutic interventions. Thus, systematic desensitization, combined with supportive therapeutic practices, proves to improve the quality of life for adolescents struggling with specific phobias. These findings not only enrich academic literature but also aid practitioners in designing interventions that are more responsive to patient needs.